Dysregulation of the MIRLET7/HMGA2 axis with methylation of the CDKN2A promoter in myeloproliferative neoplasms. (19th September 2014) - Harada‐Shirado, Kayo; Ikeda, Kazuhiko; Ogawa, Kazuei; Ohkawara, Hiroshi; Kimura, Hideo; Kai, Tatsuyuki; Noji, Hideyoshi; Morishita, Soji; Komatsu, Norio; Takeishi, Yasuchika
Summary Overexpression of high mobility group AT‐hook 2 (Hmga2), which is negatively regulated by MIRLET7 micro RNAs through 3′‐untranslated region (3′UTR), causes proliferative haematopoiesis mimicking myeloproliferative neoplasms (MPNs) and contributes to progression of myelofibrosis in mice. Thus, we investigated HMGA2 mRNA expression in 66 patients with MPNs including 23 polycythaemia vera (PV), 33 essential thrombocythaemia (ET) and 10 primary myelofibrosis (PMF). HMGA2 mRNA expression, especially variant 1 with 3′UTR that contains MIRLET7‐specific sites, rather than variant 2 lacking 3′UTR, is frequently deregulated due to decreased MIRLET7 expression in granulocytes from over 20% of PV and ET, and in either granulocytes or CD34+ cells from 100% of PMF. Patients with deregulated HMGA2 mRNA expression were significantly more likely to show splenomegaly, high serum lactate dehydrogenase values, and methylation of the CDKN2A promoter compared with other patients without deregulation of HMGA2. A histone deacetylase inhibitor, panobinostat, significantly increased MIRLET7 expression and reduced variant 1 of HMGA2 mRNA expression, but not variant 2, in both U937 cells and PMF‐derived CD34+ cells. Moreover, both panobinostat and small interfering RNA of HMGA2 demethylated the CDKN2A promoter in U937 cells. In conclusion, the frequently dysregulated MIRLET7/HMGA2 axis could be a therapeutic target in MPNs.